Do trabalho sujo à bela obra: o que é triar materiais recicláveis?: Um estudo em Psicossociologia do Trabalho - Fabiana Goulart Oliveira (2016)
The objective of this thesis is to understand the psychosocial and subjectification processes that take place in the work of collectors of recyclable materials, especially in the case of the screeners employed in recycling co-ops. Comprehension is sought of what it means to "become a collector," or of what it is that makes a collector, in the double sense of the term: the content of his or her activity and how, in performing it, the individual establishes himself as a professional. The present study questions statements by authors who defend that the discourse related to the pride and satisfaction experienced by the collectors at work would be related to defensive and ideological mechanisms that contribute to the overexploitation and alienation of such professionals. It investigates how the work of collecting recyclable materials, and in particular their screening, performed in precarious conditions that involve direct contact with dirty objects, worthless and potentially contaminating, could be a source of development for the aforementioned professionals, allowing them to recognize themselves in their own work. The research employs the ethnographic method, with a basis on action research and grounded theory. It analyzes the work of screeners of recyclable materials from the standpoint of the relationship between: the historical and political process of organization of collectors, their concrete activitymodes of operation, movements, strategies, instruments, interpersonal conflicts, and their subjective processes. As a result of this research, emphasis is given not only to the existence of a profession, with its own rules and values, but as well to the development of the professionals, which is evidenced by their transformations and the transformations in their work.